2016
DOI: 10.1016/j.pec.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and desire to improve cholesterol levels among patients with hyperlipidemia

Abstract: Objective Because hyperlipidemia is asymptomatic, many veterans affairs (VA) patients may not perceive it seriously. We assessed key Health Belief model concepts to describe patients’ cholesterol-related health beliefs and examine associations between patient-level factors and desire to improve cholesterol control. Methods We used baseline data from an ongoing randomized clinical trial. Eligible patients were receiving care at the Durham VA and had CVD risk-total cholesterol levels >130 mg/dL and/or <80% med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…For instance, reasons for drug discontinuations are rarely available in pharmacy data or primary care prescribing data, and if present, are often in narrative form [ 21 , 22 ]. Reasons for non-adherence and persistence to statins have been explored using cross-sectional surveys [ 10 , 17 , 19 , 23 32 ], with occasional qualitative approaches undertaken [ 33 , 34 ], or examination of electronic health records [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, reasons for drug discontinuations are rarely available in pharmacy data or primary care prescribing data, and if present, are often in narrative form [ 21 , 22 ]. Reasons for non-adherence and persistence to statins have been explored using cross-sectional surveys [ 10 , 17 , 19 , 23 32 ], with occasional qualitative approaches undertaken [ 33 , 34 ], or examination of electronic health records [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As applied to specific health behaviors, self-efficacy is viewed as modifiable based on experiences and behavior change interventions. Studies have correlated self-efficacy with specific health-related behaviors, such as chronic disease management, smoking cessation, diet, and exercise (Bello, Lapin, Poston, Hirshfeld, & Hosack, 2016; Hagger et al, 2016; Nezami et al, 2016; Zullig et al, 2016). Studies have also demonstrated that interventions can be effective in modifying self-efficacy for specific health-related behaviors and in improving those health behaviors (Burke et al, 2015; Sheeran et al, 2016).…”
mentioning
confidence: 99%
“…For instance, reasons for drug discontinuations are rarely available in pharmacy data or primary care prescribing data, and if present, are often in narrative form [21,22]. Reasons for non-adherence and persistence to statins have been explored using cross-sectional surveys [10,17,19,[23][24][25][26][27][28][29][30][31][32], with occasional qualitative approaches undertaken [33,34], or examination of electronic health records [21].…”
Section: Introductionmentioning
confidence: 99%